The ecologic envoy - Modesitt, L.E. Jr. 1943- (TOR science fiction, 1986)
After winning secession from the Terran Empire, the star system Accord wants to sign a simple trade treaty on microchip export tariffs. If the agreement is so minor, why is Professor Nathaniel Whaler - top economist and commando killer - chosen as envoy?